2019
DOI: 10.5603/imh.2019.0003
|View full text |Cite
|
Sign up to set email alerts
|

Is it worth to continue to analyse the factors of cardiovascular risk among the sailors? Review of literature

Abstract: Background: Cardiovascular diseases are still the most common cause of death from natural causes among seafarers. The aim of the study was to determine which of the cardiovascular risk factors listed in the current recommendations of the European Society of Cardiology occur among seafarers. Materials and methods: The paper is a review of literature from PubMed Database. Results: Based on conducted analysis of over 31 papers high prevalence of classic and other cardiovascular risk factors among seafarers was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…For sailors, cardiovascular risk control is a priority [3,4]. Because of the geographical distance, care is difficult and can be delayed.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For sailors, cardiovascular risk control is a priority [3,4]. Because of the geographical distance, care is difficult and can be delayed.…”
mentioning
confidence: 99%
“…But we do not know exactly how to quantify this consumption. In a study of 136 Filipino sailors, 80% of the subjects had consumed alcohol at least once in the month [4]. Fort et al [5] showed that 16% of the 1847 seafarers in their study were at risk of addiction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the side effects of some drugs used for comorbidities, such as selective serotonin-reuptake inhibitors, thiazides, and β-blockers, affect erectile function and thereby weaken the effect of PDE5is on ED [ 21 - 22 ]. Interestingly, unhealthy behaviors, such as excessive drinking, smoking, and a high-fat diet, can also promote the development and progression of these comorbidities in men, in turn affecting the efficacy of PDE5is in the treatment of ED [ 23 - 25 ]. Hence, lifestyle factors should be emphasized in ED treatment when there is the lack of a response to PDE5is.…”
Section: Possible Causes For Ed In Pde5i Nonrespondersmentioning
confidence: 99%
“…Зарубежными учеными приведены результаты ряда исследований. Так, исследования показателей углеводного обмена выявили повышенные уровни глюкозы в крови натощак у американских моряков [5,6], датских [7][8][9], иранских моряков [10], по сравнению с контрольной группой [11]. В другом исследовании выявлены частые случаи госпитализации германских рыбаков из-за повышенного уровня сахара в крови [12].…”
Section: T B P E T R O V a F A B I C H Kae V A R A T I O O unclassified